Exploring residents' perspectives on local energy transition in Northern Netherlands - Psarra, Ifigenia; van Ulsen, Bob; Turhan, Ethemcan; van der Schoor, Tineke (International journal of urban sustainable development, 2024)
Given the urgency of global energy transition, small- and medium-sized cities often undergo rapid changes. What is often missing, however, is a better understanding of how residents of those places perceive, and relate to the various aspects of local energy transition process and spatial outcomes. This study focuses on the Hoogkerk district of Groningen in the Northern Netherlands, where we used Q-Methodology to identify shared viewpoints. Our findings reveal three main viewpoints: a) the importance of protecting local spatial and environmental values, b) prioritising energy-saving approaches notably for the vulnerable segments of the society, and finally c) the need for comprehensive district-level planning led by the municipality. These findings underscore the importance of integrated approaches that address both spatial and process aspects of local energy transition. We argue that these insights can support policymakers and the local citizen initiative towards the development of an integrated local energy vision.